Associations between acylcarnitine to free carnitine ratio and adverse prognosis in heart failure patients with reduced or preserved ejection fraction. (26th June 2017) - Yoshihisa, Akiomi; Watanabe, Shunsuke; Yokokawa, Tetsuro; Misaka, Tomofumi; Sato, Takamasa; Suzuki, Satoshi; Oikawa, Masayoshi; Kobayashi, Atsushi; Takeishi, Yasuchika
Abstract: Aims: The failing heart is accompanied by disturbed energy metabolism with mitochondrial dysfunction. Carnitine transports fatty acids into mitochondria for β‐oxidation. Decreased myocardial carnitine levels accompanied by increased plasma carnitine levels in heart failure (HF) have been reported. The plasma acylcarnitine to free carnitine ratio (AC/FC) is recognized as a marker of carnitine deficiency. We aimed to investigate the impact of the AC/FC on HF prognosis, taking into consideration differences between HF patients with preserved ejection fraction (HFpEF) and those with reduced ejection fraction (HFrEF). Methods and results: Consecutive 168 HF patients were divided into three groups based on their AC/FC: first to third tertiles ( n  = 56, respectively). We followed up all patients for cardiac events including cardiac death and/or worsening HF. During the follow‐up period (1004 days), there were 23 cardiac deaths and 28 worsening HF. In the Kaplan–Meier analysis, the cardiac event rate of the third group was highest among the three groups ( P  = 0.022). In the Cox proportional hazard analysis, AC/FC was a predictor of cardiac events ( P  = 0.007). When HFpEF ( n  = 79) and HFrEF ( n  = 89) were analysed separately, the cardiac event rate of the third group was highest with regard to HFpEF ( P  = 0.008), but not HFrEF ( P  = 0.321). In the Cox proportional hazard analysis, AC/FC was a predictor of cardiac events with regard to HFpEF ( P  = 0.031), but not HFrEF ( P  = 0.095). Therefore, the impact of the AC/FC on cardiac events was different between HFpEF and HFrEF ( P  = 0.042 for interaction). Conclusions: The AC/FC can identify high risk HF patients, especially in HFpEF.